Anatomic description of flexor pulley system. Functional impact of injury - Mosquera-Matta, María-Camila (2023)
Introduction: The hand, as the most distal region of the upper limb, plays a crucial role in enabling fine motor skills and gripping abilities. It houses a complex system of palmodigital structures known as pulleys that support the functioning of flexor tendons during finger movements. Injuries to these pulleys can lead to aesthetic and functional impairments, significantly impacting patients' work capacity and quality of life. Hence, understanding these structures should be of great interest to medical professionals. Materials and methods: A comprehensive literature review was conducted using Medline, employing controlled terminology and advanced search equations. This review gathered 26 articles that describe the morphofunctional characteristics of the human hand's flexor pulley system and its functional implications in the event of traumatic injuries. Results: The II-V fingers possess five pulleys located between annular and cruciate regions, with annular pulleys 2 and 4 playing a pivotal role in the functioning and sliding of the flexor apparatus. In the I finger, the oblique pulley stabilizes the gripping system; however, injuries to this pulley can affect the vascular supply provided by the synovial sheaths, resulting in severe functional losses. Conclusions: The digital pulleys' specific location, configuration, and mechanism of action contribute significantly to the evolutionary advantage of the human hand, facilitating various gripping and pinching actions for daily activities. Nevertheless, their subcutaneous placement and exposure to high loads during certain work and sports activities make them susceptible to injuries, leading to motor disabilities and deformities.